2020
DOI: 10.11604/pamj.2020.37.71.24484
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of the community leaders on adolescents´ HIV: cross sectional study in Mulanje, Malawi

Abstract: Introduction the spread of HIV among adolescents requires effective interventions as new infections are high in this cohort globally. We explored perception of community leaders on the prevalence of adolescent´s HIV in Mulanje, Malawi. Methods focus group discussion (n=11) and in-depth interviews (n=15) were conducted with community leaders in all Traditional Authorities in Mulanje district, Malawi. The interviews were audio recorded and transcribed. Data were analysed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…SES, like level of education, was found to be significantly associated with teenage pregnancy. Poor families in Zimbabwe are unable to provide their teenage children with adequate basic needs such as proper food, clothing, and shelter, putting them at risk of engaging in sexual relationships with older men, increasing their chances of experiencing early pregnancy (Chimatiro et al, 2020). Similarly, Wamoyi et al…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…SES, like level of education, was found to be significantly associated with teenage pregnancy. Poor families in Zimbabwe are unable to provide their teenage children with adequate basic needs such as proper food, clothing, and shelter, putting them at risk of engaging in sexual relationships with older men, increasing their chances of experiencing early pregnancy (Chimatiro et al, 2020). Similarly, Wamoyi et al…”
Section: Discussionmentioning
confidence: 99%
“…According to Maemeko et al (2018) alcohol is a major determinant of teenage pregnancy, due to the fact that when teenagers are under its influence, they make poor decisions (Maemeko et al, 2018). This is supported by a study by Chimatiro et al (2020) in Malawi where it was found that substance addiction, particularly alcohol drinking and marijuana smoking (chamba), were among the leading factors contributing to the high rates of pregnancy among teenagers in their communities (Chimatiro et al, 2020). Furthermore Guo et al (2019) showed in their study that alcohol consumption is linked to unprotected intercourse, teenage pregnancies and abortion, particularly among teenagers who are still gaining the knowledge and abilities to regulate their sexual behaviour in appropriate ways (Guo et al, 2019).…”
Section: Alcohol Abusementioning
confidence: 92%
See 3 more Smart Citations